Measurement of the polarisation in the auroral N2+ 427.8 nm band - Barthélemy, Mathieu; Lamy, Hervé; Vialatte, Anne; Johnsen, Magnar Gullikstad; Cessateur, G; Zaourar, N (Journal of Space Weather and Space Climate, 2019)
Source at https://doi.org/10.1051/swsc/2019024. In this paper, we provide for the first time polarisation measurements of the N + 2 band at 427.8 nm performed with Premier Cru, a dedicated spectropolarimeter to investigate the polarisation of auroral emission lines between 400 and 700 nm. Details about the instrument, the observing conditions and the data analysis procedure are provided. Results obtained during three nights in March 2017 in Skibotn, Norway, indicate that the auroral blue line is polarised with a degree of linear polarisation of a few %. Due to weak Signal-to-Noise Ratios (SNR), these measurements still need to be taken with caution since none of the individual data set has a detection with a 3σ confidence level. However, results integrated over the entire observing period each night do show a 3σ detection but due to the long integration period, the origin of this polarisation cannot be linked to a specific type of aurora (diffuse vs structured arc) or specific ionospheric or geomagnetic conditions. These observations need to be confirmed with an improved design to increase the SNR and decrease the exposure time. When available, these improved measurements of the blue line polarisation will be important to better understand the physics of auroral processes at altitudes below 100 km where the N 2 + emission occurs and possibly for space weather applications if the polarisation varies with ionospheric/geomagnetic conditions.